If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(b + -3) = 4 Reorder the terms: a(-3 + b) = 4 (-3 * a + b * a) = 4 (-3a + ab) = 4 Solving -3a + ab = 4 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Reorder the terms: -4 + -3a + ab = 4 + -4 Combine like terms: 4 + -4 = 0 -4 + -3a + ab = 0 The solution to this equation could not be determined.
| 109-4x=32x+17 | | =31 | | 4a^2-5b+1=0 | | 20k^2-44k-39=0 | | 0-4x=12-7 | | 27-6=11 | | 2y-4=-11+3y | | 4x-6=4(x-2) | | 2y-4=11-3y | | 8x-7=-5x-16 | | (x/2+1)^2-1=x^2-1 | | 19-2(3x-1)/5=x+3 | | 8x-7=5x+16 | | 19-2(3x-1)/5=x+5 | | -114-8x=11-8(x)(x) | | 3(x)(x)+7x-4=11x | | 7x+4+2y=-8 | | 7x+4+2y=8 | | 7y-9=3y+3 | | -z=70 | | 20-5x=3x-60 | | 24+y-6=9y-10-4y | | (20-5x)=(3x-60) | | 6y^2+4y+4=0 | | 14f(x)=x-5 | | -10+x^2-3x=0 | | 14(x)=x-5 | | 2x^2=2400 | | 11R+17/4=-4 | | 15x^3-10x^2+9x-6=0 | | 0.08(x-100)=80.5-0.07 | | 4(-3x-4)=13x |